A health and demographic surveillance system of cattle on communal rangelands in Bushbuckridge, South Africa : baseline census and population dynamics over 12 months - Knobel, Darryn Leslie (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.